KONSEP KETAHANAN PANGAN PADA KASUS OVERFISHING PADA KAWASAN LAUT JAWA - Maria Alpha Carmelite (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2019)
As a maritime country, Indonesia is one of the largest fish producers in the world. This marine resources has fulfilled Indonesian people in their daily needs on fish and also has fulfilled the world's demands for fish. Sea of Java is one of the main ecosystems that provides that marine commodities. However the fish demand that always increases over time threatened the fish ecosystem because of overfishing phenomena by fishermen. The most possible solution for this problem is establish fisheries transmigration in Indonesia which is supported by suitable equipment for fish catching in purpose to resource and development equality in all regions of Indonesia as well as preserving marine biota conservation for marine improvement in this region for the future generation.